POLA PEMILIHAN JODOH BERDASARKAN ETNIS MINANGKABAU DI KECAMATAN TAMPAN KOTA PEKANBARU - Sari, Nurmala; ", Yoserizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research was carried out in the Tampan city of Pekanbaru. The purpose of this research is to know the factor of religion, ethnicity still made a major consideration in the determination of the Minangkabau Ethnic community partner in the Tampan city of Pekanbaru. Topic the focus of this research is to know the factors that influence the pattern of election of the Minangkabau Ethnic community partner in the Tampan city of Pekanbaru. The sample in this study amounted to 200 people. The author uses quantitative methods and use techniques of retrieval of quota Sampling. Data instruments are observation, question form and documentation. Of research conducted, the authors found that some patterns of election partner based on Minangkabau ethnic group found in the study, namely as follows: on the basis of religion, 89.5% stated that the religion of the couple's life is a characteristic the main choice in choosing a mate. Based on custom, 41.5% of the respondents still made the Minangkabau adat as a guide in choosing a mate. 58.5% of respondents choose a spouse is no longer based on custom. Based on heredity, 57% of respondents stated that lineage candidate spouse to look properly. Based on education, 49% of respondents said it is true that education plays an important role in the choice of life partner. Based on the job, 29.5% of respondents stated that the work actually be one of the characteristics of respondents in choosing a mate. Based on Property/objects, 40% of respondents stated that the couple's possessions affect the decision of choosing a partner. Though not a lot, but the fact the percentage tends to be high. Keywords: Wedding, Rational Choice, Minangkabau